2014
DOI: 10.1038/srep06365
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms increase plant production: a meta-analysis

Abstract: To meet the challenge of feeding a growing world population with minimal environmental impact, we need comprehensive and quantitative knowledge of ecological factors affecting crop production. Earthworms are among the most important soil dwelling invertebrates. Their activity affects both biotic and abiotic soil properties, in turn affecting plant growth. Yet, studies on the effect of earthworm presence on crop yields have not been quantitatively synthesized. Here we show, using meta-analysis, that on average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
276
5
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(329 citation statements)
references
References 37 publications
(39 reference statements)
21
276
5
4
Order By: Relevance
“…Earthworms act as a catalyst in enhancing the crop yield (Table 1), but their effect depends on the amount of crop residue, earthworm density and rate of fertilization 9 . However, they always provide materials and energy outputs which have monetary values.…”
mentioning
confidence: 99%
“…Earthworms act as a catalyst in enhancing the crop yield (Table 1), but their effect depends on the amount of crop residue, earthworm density and rate of fertilization 9 . However, they always provide materials and energy outputs which have monetary values.…”
mentioning
confidence: 99%
“…The positive effect of earthworms on plant growth and health (Brown et al, 1999;Scheu, 2003;Van Groenigen et al, 2014) is now well documented, and could be used in the development of alternative pest management strategies (Blouin et al, 2005;Senapati, 1992;Davoren, 1995, 1997;Wurst et al, 2008;Wurst, 2010;Yeates, 1981). However, further investigations of the mechanisms underlying this positive effect are required, to distinguish between the effects of earthworms on pathogens and their direct effects on plants.…”
Section: Resultsmentioning
confidence: 99%
“…2003; Van Groenigen et al, 2014), which could prevent infection. These mechanisms are likely toact in synergy.…”
Section: Eyespot Symptoms and Their Biological Control By Earthwormsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Johnson-Maynard et al (2007) reported significantly higher earthworm densities in conservation tillage treatments as compared to conventional tillage in the annual cropping zone of the iPNW. Earthworms are important biological indicators of soil quality and can increase biodiversity and yields in managed systems (van Groenigen et al, 2014).…”
Section: Reduced Tillage and Crop Residue Managementmentioning
confidence: 99%